(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2026)
The research aims to demonstrate the role that value engineering can play in cost management and the implementation of a differentiation strategy by providing low-cost, high-quality products. The focus is on two aspects: price and cost. This is achieved by demonstrating the role of this technology in reducing costs, thereby reducing the selling price. It also focuses on quality and ensuring that the product meets specifications and customer needs and requirements. The research was conducted at the General Company for Electrical Industries/Fan Factory, using data from 2021. Value engineering was applied in this factory, and a functional analysis of product components was conducted. The research reached a set of conclusions, the most important of which was that value engineering assists in cost management by identifying areas where cost reductions can be implemented with the aim of standardizing procedures, which in turn leads to cost reductions, as well as improving the quality of both processes and products. This, in turn, enhances quality from the perspective of both the customer and the economic unit, leading to efficient and effective implementation of the differentiation strategy.